A rugged high-throughput analytical approach for the determination and quantification of multiple mycotoxins in complex feed matrices - Dzuman, Zbynek; Zachariasova, Milena; Lacina, Ondrej; Veprikova, Zdenka; Slavikova, Petra; Hajslova, Jana (Talanta, 2014)
We have developed and optimized high throughput method for reliable detection and quantification of 56 Fusarium, Alternaria, Penicillium, Aspergillus and Claviceps mycotoxins in a wide range of animal feed samples represented by cereals, complex compound feeds, extracted oilcakes, fermented silages, malt sprouts or dried distillers' grains with solubles (DDGS). From three tested extraction approaches (acetonitrile, acetonitrile/water, and QuEChERS), the QuEChERS-based method (Quick, Easy, Cheap, Effective, Rugged and Safe) was selected as the best in terms of analytes recoveries and low matrix effects. For separation and detection of target mycotoxins, method based on ultra-high performance liquid chromatography coupled with sensitive tandem mass spectrometry (U-HPLC-MS/MS) was employed. With regards to a high complexity of most of investigated feed samples, optimization of extraction/purification process was needed in the first phase to keep the method as rugged as possible. A special attention was paid to the pH of extraction solvents, especially with regard to the pH-sensitive silages. Additionally, purification of the acetonitrile extract by dispersive solid phase clean-up was assessed. Significant elimination of lipidic compounds was observed when using C18 silica sorbent. Matrix co-extracts were characterized by ultra-high performance liquid chromatography coupled with ultra-high resolution mass spectrometry (U-HPLC-HRMS). Large variability of matrix effects depending on the nature of examined feed was demonstrated in depth on a broad set of samples. Simple and unbiased strategies for their compensation were suggested.
Keywords: Dispersive solid phase extraction; QuEChERS; Tandem Mass Spectrometry; Matrix effects; Chromatography, High Pressure Liquid; Animal feed; Ultra-high performance liquid chromatography coupled with tandem mass spectrometry; vysokoúčinná kapalinová chromatografie; Mycotoxins; Animal Feed; Animals; tandemová hmotnostní spektrometrie; krmivo pro zvířata; zvířata; mykotoxiny